The babel of European Union studies: beyond the trans-Atlantic divide. Issue 3 (September 2018) - Jensen, Mads; Kristensen, Peter
Abstract This article examines four lines of scholarly difference in European Union (EU) studies – meta-theoretical, (sub)disciplinary, epistemological and methodological – and whether these are linked to the geographical and institutional affiliations of the authors operating in the field. The study uses a novel dataset based on a quantitative content analysis and human coding of 1597 articles in leading journals dealing with the EU published in the period 2003–2012. The article shows that USA-based scholars score on average – though in many cases, not significantly – higher when it comes to indicators of a comparative politics approach to the EU, use of a rational choice, positivist and statistical vocabulary, and articles coded as quantitative. However, on most of these indicators scholars in some European countries, and especially some institutions, score significantly higher, suggesting that we should disaggregate 'Europe' when discussing scholarly differences in the field.